Interculturality library and museum: a case study of the Sesc Ler Goiana unit on cultural actions to strengthen local heritage - Silva , Danielle Martins da; Silva , Ketheleen Vieira da; Nunes Pires de Oliveira , Tayná; Sousa , Vinícius Felipe de Lima; Terra, Guilhermina de Melo (Ciência da Informação em Revista, 2024)
The aim of this article is to list the socio-educational and cultural activities carried out by the Sesc Ler Goiana Library and the Maximiano Campos Museum of Sacred Art, highlighting, above all, the intercultural activities carried out to make their spaces more dynamic and bring them closer to their users, and analyzing whether these activities contribute to the territory where both facilities are located, the municipality of Goiana, in Pernambuco, Brazil, from the perspective of strengthening cultural heritage. The theoretical context deals with the concepts of culture and cultural action in libraries. Methodologically, it is characterized as exploratory-descriptive research, based on a case study, which focused on the actions developed jointly by the information equipment of the Sesc Ler Goiana unit, from 2019 to 2023. The results of the research show that both have fulfilled their role as equipment for promoting culture, literature and leisure. The conclusion is that it is possible for information professionals to act as cultural agents, building ways to bring different audiences closer to the Library and Museum